The papers of Henry Clay. - Hopkins, James F.; Hargreaves, Mary W. M., 1914-2008 (University of Kentucky Press, 1961)
Henry Clay's career spanned a half century of a great formative period in American history. This compilation of ten volumes includes Clay's letters, letters to Clay, his speeches, and other documents identified as his personal composition.